Evaluación de enfermedades fungosas del arbolado urbano de las avenidas de la ciudad de Loja - Troya Alverca, Danny Israel (2023)
In the city, trees can mitigate climate change and improve social welfare, which are preponderant factors to improve the quality of life. The silvicultural management of this resource is limited exclusively to the execution of training and pruning, neglecting the phytosanitary aspect; thus, this research is framed in the field of plant health by examining fungal diseases present in urban trees in the main avenues of the city of Loja, determining the symptomatology and identifying the causal agent. The methodology used was qualitative and descriptive. In the field, 10 most abundant species present in the avenues were evaluated. Consideration was made for 30% of individuals for each species. The specimens were taken to the laboratory for isolation in a humid chamber, culture medium and identification of the causal agent by morphological keys. The symptoms identified were: blackish scab, affecting the species Jacaranda mimosifolia; causal agent Fumagina (Capnodium sp), Alnus acuminata; causal agent Roya (Melamporidium alni). Macha necrotica; Salix humboldtiana, causal agent Fumagina (Melampsoridium alni), Fraxinus chianensis, causal agent Alternaria (Alternaia sp), Lafoensia acuminata. Causal agent Alternaria (Alternaia sp). Alternaria (Alternaia species) causes yellowing in Acacia macracantha, Jacaranda mimosifolia, and Grevillea robusta. The species with the highest incidence of symptoms were Fraxinus chinensis, Alnus acuminata and Acacia macracantha. These are the most affected species; the urban trees in the avenues of the city of Loja show symptoms and signs of primary fungal diseases such as Alternaria, Rust and Fumagina. Key words: urban trees, symptomatology, causal agent, Loja.